2016
DOI: 10.1128/aac.00945-16
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Leishmania mexicana Growth by the Tuberculosis Drug SQ109

Abstract: We report that the tuberculosis drug SQ109 [N-adamantan-2-yl-N=-((E)-3,7-dimethyl-octa-2,6-dienyl)-ethane-1,2-diamine] has potent activity against the intracellular amastigote form of Leishmania mexicana (50% inhibitory concentration [IC 50 ], ϳ11 nM), with a good selectivity index (>500). It is also active against promastigotes (IC 50 , ϳ500 nM) and acts as a protonophore uncoupler, in addition to disrupting Ca 2؉ homeostasis by releasing organelle Ca 2؉ into the cytoplasm, and as such, it is an interesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…While MmpL3 is conserved in mycobacteria, functional orthologs are not found in other bacteria and fungi. Despite this, several proposed MmpL3 inhibitors including BM212, THPP, and SQ109 have been shown to inhibit multiple bacterial and fungal species 8, 33, 34, 35 while other MmpL3 inhibitors including HC2091, AU1235, and indolecarboxamides are specific to mycobacteria. To define the spectrum of activity, the compounds were tested against several diverse species including Staphylococcus aureus, E. coli, Pseudomonas aeruginosa, Proteus vulgaris , and Enterococcus faecalis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…While MmpL3 is conserved in mycobacteria, functional orthologs are not found in other bacteria and fungi. Despite this, several proposed MmpL3 inhibitors including BM212, THPP, and SQ109 have been shown to inhibit multiple bacterial and fungal species 8, 33, 34, 35 while other MmpL3 inhibitors including HC2091, AU1235, and indolecarboxamides are specific to mycobacteria. To define the spectrum of activity, the compounds were tested against several diverse species including Staphylococcus aureus, E. coli, Pseudomonas aeruginosa, Proteus vulgaris , and Enterococcus faecalis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…There has been some controversy as to the direct or indirect inhibition of these compounds against MmpL3, it has been suggested that some compounds may act indirectly on MmpL3 by disrupting the pH gradient and/or membrane potential which will disrupt the proton relay needed by MmpL3 to pump out TMM. Indeed, while SQ109 and BM212 display a broad spectrum of activity and are active against non-replicating Mtb bacilli, some others specifically target mycobacteria and do not kill nonreplicating bacilli [16,103,104]. In order to solve this controversy and to shed more light on the mechanism of action of these inhibitors, Li et al have recently developed assays both in vitro and in whole cells to identify direct inhibitors of MmpL3.…”
Section: Mmpl3: the Achilles Heel Of Mycobacterium Tuberculosismentioning
confidence: 99%
“…With regard to Ca 2ϩ signaling, it is known that the mechanisms involved in Ca 2ϩ regulation in trypanosomatids constitute a target for chemotherapeutic agents like amiodarone and dronedarone, which disrupt Ca 2ϩ homeostasis in T. cruzi and L. mexicana (21)(22)(23)(24) through their action on two organelles acting as Ca 2ϩ compartments, the mitochondrion and the acidocalcisomes. Moreover, the antituberculosis compound SQ109, which also possesses a very potent trypanocidal effect, was recently found to act on T. cruzi (25) and L. mexicana (26) through the same mechanism of Ca 2ϩ and mitochondrial disruption. Also in concerns to disruption of Ca 2ϩ regulation, it has been reported that many Ca 2ϩ channel antagonists produce a marked effect in several trypanosomatids (27), including L. donovani (28).…”
mentioning
confidence: 99%